Lyrical singers: duets with anxiety - Ferreira, Marlene (2019)
Introduction: This article describes and analyses the partial results of a broad qualitative study, whose goal was to explore how performance anxiety is presented in the everyday life of the lyrical singer. Objectives: The daily life changes before a recital and what strategies are used in the their confrontation by this group of professionals. Methods: The results presented are centered in the production of discourse from three questions covering the experience of anxiety on musical performance, and the eventual strategies applied to overcome it. These data were gathered using a social-professional questionnaire and a semi-structured interview addressed to a group of 8 lyric singers with over 6 years of experience, sampled through the snowball method. Grounded Theory was the procedure chosen to access the emerging constructs in the participants’ discourses, following the routines of analysis unit selection, memorandum generation and categorization on two levels (descriptive and conceptual). Results: The method focuses on the production of the speeches concerning three question about the experience of musical performance anxiety, daily routines adopted in the pre-recital period and the eventual strategies used to overcome anxious symptomatology. Conclusions: The collected results recognize the harmful impact of performance, a constant conviviality with the anxiety and consequent changes in daily life routines at personal and social level, leading to the adoption of strategies for anxiety control.